2017
DOI: 10.1007/s10532-017-9801-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of methyl parathion degradation by a Burkholderia zhejiangensis strain, CEIB S4-3, isolated from agricultural soils

Abstract: Through the use of an enrichment technique, we isolated from the agricultural soils of Morelos in central México a strain of Burkholderia zhejiangensis identified as CEIB S4-3, it's could use the pesticide methyl parathion (MP) as the only source of carbon and degrade completely p-nitrophenol (PNP). For more efficient MP and PNP degradation by the CEIB S4-3 strain, the absence of an extra carbon source, a large inoculum and an MP concentration up to 50 mg/l are required. Sequence and annotation analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The genomic data revealed that B. zhejiangensis CEIB S4-3 has a methyl parathion degrading ( mpd ) gene with 99% identity with respect to the gene MpdB, which was identified in B. cepacia by Ekkhunnatham et al (2012), which codes for a methyl parathion hydrolase (MPH) enzyme. Furthermore, this data also reveals that this strain has two PNP catabolic gene clusters, pnpABA′E1E2FDC and pnpE1E2FDC (Hernández-Mendoza et al, 2014; Popoca-Ursino et al, 2017). The alignment between the two PNP proteins of B. zhejiangensis CEIB S4-3 and Burkholderia sp.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…The genomic data revealed that B. zhejiangensis CEIB S4-3 has a methyl parathion degrading ( mpd ) gene with 99% identity with respect to the gene MpdB, which was identified in B. cepacia by Ekkhunnatham et al (2012), which codes for a methyl parathion hydrolase (MPH) enzyme. Furthermore, this data also reveals that this strain has two PNP catabolic gene clusters, pnpABA′E1E2FDC and pnpE1E2FDC (Hernández-Mendoza et al, 2014; Popoca-Ursino et al, 2017). The alignment between the two PNP proteins of B. zhejiangensis CEIB S4-3 and Burkholderia sp.…”
Section: Introductionmentioning
confidence: 56%
“…Previously, information about the strain Burkholderia zhejiangensis CEIB S4-3, which was isolated from agricultural soils from the state of Morelos, in central Mexico, was reported. This strain was found to have the ability to hydrolyze MP, to degrade PNP and to use the byproducts as a carbon source when cultured in the presence of 0.2 mM of MP in liquid fermentation (Popoca-Ursino et al, 2017). The strain B. zhejiangensis CEIB S4-3 is able to hydrolyze MP pesticide in 1 h and completely degrade PNP in 12 h. The analysis of a draft genome of this strain (Hernández-Mendoza et al, 2014) revealed the presence of several genes that encode sequences that are highly similar to previously characterized enzymes related to the hydrolysis of MP and the degradation of PNP in Burkholderia sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the retention time for standard methyl parathion was 3.433 minutes with the peak area of 7.345 mV.s and peak height of 0.444 mV (Fig.8) in HPLC analysis. Burkholderia cepacia which has a potential methyl parathion degrading ability from agricultural soil was isolated [44]. Table 1…”
Section: Uv-visible Spectrophotometrymentioning
confidence: 99%
“…Mangrove peat (Natália Alvarenga et al, 2018) Burkholderia sp. (Fernández-López et al, 2017;Popoca-Ursino, Martinez-Ocampo, Dantan-Gonzalez, Sanchez-Salinas and Ortiz-Hernandez, 2017) Klebsiella sp. (Pattanayak, Chakraborty, Biswas, Chattopadhyay and Chakraborty, 2018) Fischerella sp.…”
Section: Methyl Parathionmentioning
confidence: 99%